2011
DOI: 10.1890/100071
|View full text |Cite
|
Sign up to set email alerts
|

The influences of wolf predation, habitat loss, and human activity on caribou and moose in the Alberta oil sands

Abstract: Woodland caribou (Rangifer tarandus caribou) and moose (Alces alces) populations in the Alberta oil sands region of western Canada are influenced by wolf (Canis lupus) predation, habitat degradation and loss, and anthropogenic activities. Trained domestic dogs were used to locate scat from caribou, moose, and wolves during winter surges in petroleum development. Evidence obtained from collected scat was then used to estimate resource selection, measure physiological stress, and provide individual genetic ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
136
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(148 citation statements)
references
References 20 publications
11
136
1
Order By: Relevance
“…To our knowledge, this is the first longitudinal study on Rangifer to present data on both faecal cortisol and corticosterone metabolites from the same samples (Freeman, 2008; Ashley et al ., 2011; Wasser et al ., 2011; Macbeth, 2013; Yin et al ., 2015), and it has revealed several noteworthy patterns that would have been missed in a cross-sectional study. First, analysis revealed what appears to be a 21 day cyclic pattern in faecal cortisol levels that was not present in faecal corticosterone levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first longitudinal study on Rangifer to present data on both faecal cortisol and corticosterone metabolites from the same samples (Freeman, 2008; Ashley et al ., 2011; Wasser et al ., 2011; Macbeth, 2013; Yin et al ., 2015), and it has revealed several noteworthy patterns that would have been missed in a cross-sectional study. First, analysis revealed what appears to be a 21 day cyclic pattern in faecal cortisol levels that was not present in faecal corticosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…Our results even raise the question of whether low to moderate infection intensities with helminths are beneficial for the host, a scarcely explored hypothesis in wildlife. Glucocorticoids may still reflect exposure to other environmental stressors in Rangifer , such as anthropogenic disturbance (Wasser et al ., 2011), and provide conservation-relevant information. However, we caution against the use of stress measurements in isolation from other health and population viability indices until we have a better understanding of what the relationships between these measurements are.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the specific part of the faeces collected may affect the DNA quality and the amplification success (Rutledge et al, 2008;Gobush et al, 2009;Stenglein et al, 2010;Vynne et al, 2011;Wasser et al, 2011). This is because DNA from faeces is obtained from sloughed epithelial cells of the intestinal lining of the focal species (Albaugh et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Our study focused on the Canadian eastern boreal forest within the southern part of the continuous range of boreal caribou. The sensitivity of boreal caribou to human-induced disturbances (e.g., logging [12]; roads [13]; petroleum and natural-gas infrastructures [14]) is well-documented throughout its distributional range in Canada. Further, these disturbances are thought to be the main causes of range recession in eastern North America [15–18].…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis of climate-driven selection assumes that previously known geographic gradients are a surrogate for climatic gradients in temperature and precipitation and that selection of certain habitats varies along climatic zones. The road-driven selection hypothesis reflects a trade-off between security and nutrition in which the boreal caribou adjusts its selection of certain habitat classes as a function of distance to roads [13,27]. The additive hypothesis considers that both mechanisms act in concert.…”
Section: Introductionmentioning
confidence: 99%